META ANALYSIS: A METACOGNITION APPROACH TO STUDENTS' MATHEMATICAL PROBLEM SOLVING ABILITIES - Azizah, Maharani Nuur; Junaedi, Iwan; Susilo, Bambang Eko (FKIP Universitas Muhammadiyah Tangerang, 2024)
Problem solving is an important element in solving real life problems. When students are solving mathematical problems, students are faced with several challenges such as difficulty in understanding the problem because of problems that students have faced before. From the results of the teaching and learning activities that have been carried out, it can be concluded that the questions given to 36 students show that students' problem solving abilities are still low. The average obtained was 63.75 and classical completeness was 67%. Based on the results of the PISA survey in 2018, Indonesia was ranked 64th out of 65 countries that took part in the test. The aim of this research is to determine the increase in problem solving abilities using a metacognitive approach. This research uses a meta-analysis method by reviewing several articles in national and international journals. This meta-analysis is quantitative because it uses numerical calculations and statistics. This meta-analysis research uses 12 samples of relevant journals in national journals. Based on the results of the meta-analysis, it can be concluded that the articles that have been analyzed have an effect size value in the very high category of 17% of all articles, an effect size in the negligible category of 17%, an effect size in the high category of 17% of all articles. . The effect size in the medium category is 17% of the entire article. The effect size in the low category is 25% of the entire article. Based on the calculation results, the t_count value was 9.63 and the t_table value was 1.96; Thus the conclusion is obtained t_count=9.63>t_tabel=1.96. So H_0 is rejected. So, the average problem solving ability of experimental group students is more than the average of control group students.